1981
DOI: 10.1029/gl008i008p00927
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of middle‐atmosphere electric fields and associated electrical conductivities

Abstract: A simple antenna for measuring the vertical electric field in the "middle atmosphere" has been flown on a number of rocket‐launched parachute‐borne payloads. We present here the data from the first nine such flights, launched under a variety of geophysical conditions, along with electrical conductivities measured simultaneously. The data include indications of layered peaks of several volts per meter in the mesospheric field at high and low latitudes in situations of relatively low conductivity. During an auro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 12 publications
4
24
0
Order By: Relevance
“…This is precisely what was observed by day and night near the equator off the coast of Kenya [6]. This is precisely what was observed by day and night near the equator off the coast of Kenya [6].…”
Section: -10-13supporting
confidence: 88%
See 1 more Smart Citation
“…This is precisely what was observed by day and night near the equator off the coast of Kenya [6]. This is precisely what was observed by day and night near the equator off the coast of Kenya [6].…”
Section: -10-13supporting
confidence: 88%
“…Balloon-borne measurements performed from the ground up to the altitude of 30 km have shown that air conductivity increases with altitude by more than two orders of magnitude, while the atmospheric electric field undergoes a corresponding decrease [4]. But rocket-borne measurements in the mesosphere have revealed that at altitudes of 55-70km the electric-field strength exhibits a sharp increase up to 4-5V/m [5,6]. But rocket-borne measurements in the mesosphere have revealed that at altitudes of 55-70km the electric-field strength exhibits a sharp increase up to 4-5V/m [5,6].…”
mentioning
confidence: 99%
“…Large vertical ®elds with strength exceeding $1 V/m have been detected in the lower mesosphere during nearly all of these measurements. The experiments carried out with the help of a double probe technique have also shown these large vertical ®elds but only occasionally (Hale and Croskey, 1979;Hale et al, 1981;Maynard et al, 1981Maynard et al, , 1984Hale, 1984;Croskey et al, 1985Croskey et al, , 1990. By now, some regularities concerning the electric ®eld behaviour in the mesosphere have been clari®ed (Bragin et al, 1981;Goldberg, 1984Goldberg, , 1989Goldberg and Holzworth, 1991;Zadorozhny et al, 1989Zadorozhny et al, , 1994aZadorozhny and Tyutin, 1997).…”
Section: Introductionmentioning
confidence: 93%
“…A vertical electric field antenna similar to those described in a companion paper (Hale, et al 1981) was flown on the mother payload. A peaked electric field was also observed, and is shown in Figure 4.…”
Section: Introductionmentioning
confidence: 99%